Spektrum Sinkretisme Kristologis di Asia Kecil Pasca-Nicea (325-451 M) - Hendi; Yusuf Slamet Handoko (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2026)
Abstract This study examines Christological syncretism in post-Nicene Asia Minor (AD 325–451), moving beyond the traditional orthodoxy–heresy dichotomy. Using an interdisciplinary library research approach, it synthesizes textual evidence, including patristic writings and hagiographies, with archaeological evidence such as architecture, funerary art, and amulets. The findings demonstrate that Christological syncretism functioned along a dynamic spectrum rather than as a single phenomenon. Three operational levels are identified: conscious adaptation, in which pre-Christian forms were reinterpreted without altering Christian doctrine; pragmatic fusion, where Christ’s name and power were incorporated into local ritual practices; and conceptual assimilation, in which Christ’s nature was redefined through regional cultural narratives. The study concludes that syncretism was not merely doctrinal deviation but a significant mechanism of inculturation. By proposing a spectrum model of Christological syncretism, this research offers a nuanced analytical framework for understanding the diversity of lived Christianity in Late Antiquity.